Reducing deviant behavior through workplace spirituality and job satisfaction - Ahmad, Aminah; Omar, Zoharah (Canadian Center of Science and Education, 2014)
Despite the growing number of studies on workplace spirituality, there is still lack of studies that have explored the relationships between workplace spirituality, job attitudes and behaviors. The purpose of this paper is to propose a model on the relationship between workplace spirituality and workplace deviant behaviour with job satisfaction as a mediator. Workplace spirituality is expected to correlate negatively with workplace deviant behaviour and positively with job satisfaction, and job satisfaction is expected to correlate negatively with workplace deviant behaviour. Drawing from social control theory, social exchange theory and previous literature, we hypothesize that job satisfaction mediates the relationship between workplace spirituality and workplace deviant behaviour. According to this proposed model, an employee who experienced workplace spirituality is more likely to be satisfied with work and will not engage in workplace deviant behaviour. Given the potential effect of workplace spirituality on workplace deviant behaviour via job satisfaction, there is a need for organizations to create a culture of spirituality at the workplace.